Papaya Shredded Processing Training as a Business Opportunity for KKN Students in Brumbungan Lor Village - Abdillah, Hartawan; Zuhro, Mimik Umi; Baihaqi, Ahmad; Fathiyah, Siti; Candrayani, Dini Cipta (Abdi Masyarakat, 2023)
Probolinggo is one of the regencies that is famous for its abundant papaya fruit income, this is one of the interesting ingredients to be created by the nation's children in order to stabilize the Indonesian economy. The utilization of papaya fruit is an interesting business opportunity to be pursued, in meeting these objectives, this research article is published which focuses on processing young papaya into shredded which has a high and healthy taste that can be consumed as a substitute for side dishes, and for snacks from children to adults, as well as training in the Brumbungan Lor Village Community. The samples used in this study were 3 young papaya fruits obtained around Brumbungan. The processing technique was done by shredding, draining and frying. The result is shredded papaya which has a high taste and produces a distinctive color, taste, and aroma.